2019
DOI: 10.3389/fphar.2019.00590
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Glucose Transporter 1/Pyruvate Kinase M2 Glycolytic Loop Is Required for Cantharidin Inhibition of Metastasis in Highly Metastatic Breast Cancer

Abstract: Aerobic glycolysis plays a decisive role in cancer growth. However, its role in cancer metastasis was rarely understood. Cantharidin a natural compound from an arthropod insect cantharis exerts potent anticancer activity. Here we found cantharidin possesses significant anti-metastatic activity on breast cancer dependent on inhibition of aerobic glycolysis. Cantharidin indicates significant inhibition on migration and invasion of breast cancer cells, angiogenesis in vitro , and inhibits b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…This sesquiterpenoid bioactive compound is secreted by beetles of the family of Meloidae [155]. Although it has been available for almost a century, its use has not been approved due to its high toxicity to the gastrointestinal tract.…”
Section: Cantharidinmentioning
confidence: 99%
See 1 more Smart Citation
“…This sesquiterpenoid bioactive compound is secreted by beetles of the family of Meloidae [155]. Although it has been available for almost a century, its use has not been approved due to its high toxicity to the gastrointestinal tract.…”
Section: Cantharidinmentioning
confidence: 99%
“…It was concluded that cantharidin inhibits nuclear translocation of pyruvate kinase isoform M2 (PKM2), which promotes the transcription of GLUT1. So, cantharidin interferes with the glycolytic metabolic loop between GLUT1 and PKM2 [155] (Table 3).…”
Section: Cantharidinmentioning
confidence: 99%
“…Glycolic metabolite methylglyoxal promotes extracellular matrix remodeling and activation of the pro-migratory signaling pathway, MEK/ERK/SMAD1 in estrogen receptor-positive (ER+) and TNBC cell lines (7). Inversely, treatment of breast cancer cells and xenografts with natural compound cantharidin inhibited migration, invasion, angiogenesis, and metastasis by increasing oxygen consumption and suppressing aerobic glycolysis (8). Furthermore, increased oxygen consumption and dependence on oxidative metabolism through the expression of good prognostic marker B-cell lymphoma two associated death promoter (BAD) resulted in large but non-aggressive breast tumors (9).…”
Section: Introductionmentioning
confidence: 99%
“…Divulging this mechanism, they highlighted that CTD can inhibit pyruvate kinase (PK), which causes blockage in pyruvate kinase M2 (PKM2) translocation to the nucleus. This process leads to the downregulation of GLUT1/PKM2 loop which is essential for glucose transport and glycolytic metabolism [ 17 ]. CTD attenuated proliferation and migration of pancreatic cancer cells as a consequence of β-catenin-directed repression of Wnt/β-catenin signaling pathway [ 59 ].…”
Section: Anticancer Attributes Of Ctdmentioning
confidence: 99%
“…The anticarcinogenic efficacy of this terpenoid toxin was first highlighted by Chen et al around four decades back (1980) [ 16 ]. After it, further researches were conducted to elucidate its antitumor effects and finally, it has been revealed that its anticancer activity is mainly due to the inhibition of protein phosphatase 1 (PP1) and protein phosphatase type 2A (PP2A) [ 17 ]. Moreover, it has also been proven that CTD can inhibit expression level of HSP70 and BAG3 proteins by preventing heat shock transcription factor 1 (HSF-1) binding to its promoter [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%